Teroka-Histori Legiun Mangkunegaran dari Gedung Kavallerie-Artillerie - Galih Pranata; Fathan Arga Alfausta Marsetyo (UIN Imam Bonjol Padang, 2024)
The cultural heritage building, the Kavallerie-Artillerie building, has become a medium for historical exploration as an important building of its time that represents the toughness and splendor of the Mangkunegaran Legion. This article aims to examine the history behind the Kavallerie-Artillerie, a bit of the historical story about the Mangkunegaran Legion, architectural art and the current condition of the Kavallerie-Artillerie. The results of this research show that the Mangkunegara Legion is a special military unit owned by the Mangkunegaran Duchy and is considered by historians to be the first indigenous army unit in Indonesia, where their main headquarters is called the Kavallerie-Artillerie. In fact, both the information about the heritage building and the Mangkunegaran Legion, as well as the current condition of this cultural heritage building appear to have been untouched by the authorities' revitalization agenda and its function as a residential area for local residents.